Nursing Students’ Satisfaction: A Comparison between Medium- and High-Fidelity Simulation Training - Alconero-Camarero, Ana Rosa; Sarabia-Cobo, Carmen María; Catalán-Piris, María José; González-Gómez, Silvia; González-López, José Rafael (International journal of environmental research and public health, 2021)
Training based on clinical simulation is an effective method of teaching in nursing. Nevertheless, there is no clear evidence about if it is better to use high- or medium-fidelity simulation. The aim is to analyse if students are more satisfied when their clinical simulation practices are based on high-fidelity simulation (HFS) or medium-fidelity simulation (MFS). Students´ satisfaction was assessed using the Satisfaction Scale Questionnaire with High-Fidelity Clinical Simulation. The sample is composed of 393 students from two Spanish Universities. Satisfaction with simulation in nursing students is significantly greater in MFS than HFS. Simulation is beneficial for learning in all its forms, but for the acquisition of basic skills, and at a lower cost, MFS proves to be effective. However, high-fidelity is not always better than medium-fidelity as this depends on the student’s level of knowledge and clinical experience.